2016
DOI: 10.3928/02793695-20160518-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Separation on the Behavioral Health of Military Wives

Abstract: In the current prospective observational study, the impact of short-term separation on female spouses of male military officers who were scheduled to participate in a resident training program was evaluated. Using pre- and post-survey designs, participants were assessed 2 weeks prior to separation and 2 weeks prior to their husbands' returns. Participants completed the following scales: the Multidimensional Scale of Perceived Social Support, Connor-Davidson Resilience Scale, Perceived Stress Scale, Relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…The link is a strong one: Not only do people's depressive symptoms correspond with both their own and their partner's concurrent relationship satisfaction (Whisman et al, 2004), but a bidirectional association exists between depressive symptoms and relationship satisfaction over time (e.g., Gustavson et al, 2012;Roberson et al, 2018;Whitton & Whisman, 2010). Within military populations, depressive symptoms and relationship satisfaction are negatively correlated among both service members (Foran et al, 2011;Knobloch & Theiss, 2011) and their romantic partners (Dolphin et al, 2015;Oblea et al, 2016). Explanations for why people grappling with depressive symptoms are less satisfied with their romantic relationship are complicated, as noted by scholars investigating both civilians (Gustavson et al, 2012) and service members (Knobloch & Theiss, 2011).…”
Section: Depressive Symptoms and Relationship Satisfactionmentioning
confidence: 99%
“…The link is a strong one: Not only do people's depressive symptoms correspond with both their own and their partner's concurrent relationship satisfaction (Whisman et al, 2004), but a bidirectional association exists between depressive symptoms and relationship satisfaction over time (e.g., Gustavson et al, 2012;Roberson et al, 2018;Whitton & Whisman, 2010). Within military populations, depressive symptoms and relationship satisfaction are negatively correlated among both service members (Foran et al, 2011;Knobloch & Theiss, 2011) and their romantic partners (Dolphin et al, 2015;Oblea et al, 2016). Explanations for why people grappling with depressive symptoms are less satisfied with their romantic relationship are complicated, as noted by scholars investigating both civilians (Gustavson et al, 2012) and service members (Knobloch & Theiss, 2011).…”
Section: Depressive Symptoms and Relationship Satisfactionmentioning
confidence: 99%
“…13 Perceptions of having greater overall family and friend support, and family support from the military may ameliorate stressors of military spouses and improve overall well-being. [14][15][16] Additionally, military spouses benefit from seeking support and sharing experiences with other military spouses who fully understand the day-to-day challenges of being a military spouse and are seen as trusted resources. 5…”
Section: Military Spouses and Social Supportmentioning
confidence: 99%
“…In the Army Families Federation (AFF) Command Brief, 79% of spouses stated that they had compromised on the wellbeing and mental health of the non-serving family members to varying degrees [10]. Research has suggested that social support often mitigates the psychological effects of military-induced separations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%